METHODOLOGY FOR TEACHING MEDICAL TERMS IN MEDICAL FOREIGN LANGUAGE PRACTICE IN PARAMEDICINE (World Bulletin of Public Health, 2024)
Our goal is to analyze in detail the basic modern systems of methods for teaching foreign languages and show their methodological importance in terms of efficiency in teaching foreign languages.
Keywords: Lexical Syllabus; Western European languages; teaching method